1981
DOI: 10.1002/mma.1670030126
|View full text |Cite
|
Sign up to set email alerts
|

Condition number of matrices derived from two classes of integral equations

Abstract: We investigate some integral equations, i. a. the so‐called Kupradze functional equations, where the two variables of the kernel belong to two different point sets. An extensive survey of the literature shows the various applications of these equations. By a discretization of the integral equations they are replaced by systems of linear algebraic equations. The condition number of the corresponding matrices is investigated, analytically and numerically. It is thereby quantitatively found in which way the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…(36) Figure 2 shows the graph of the condition number of A as a function of radius R. We perform calculations for N = 8 (red), N = 12 (blue), N = 16 (black), and N = 20 (green), cf [2]. We observe that for increasing N the condition number also increases.…”
Section: Dirichlet Conditionsmentioning
confidence: 98%
See 1 more Smart Citation
“…(36) Figure 2 shows the graph of the condition number of A as a function of radius R. We perform calculations for N = 8 (red), N = 12 (blue), N = 16 (black), and N = 20 (green), cf [2]. We observe that for increasing N the condition number also increases.…”
Section: Dirichlet Conditionsmentioning
confidence: 98%
“…It is a well-known fact that the condition number of the system matrix is at least order N , where N is the number of boundary elements, [1]. In [2] the Dirichlet BVP for the Laplace equation is studied, where two domains are taken into account: a circle and an ellipse. In both cases analytical expressions for the condition number are derived.…”
Section: Introductionmentioning
confidence: 99%
“…has a non-trivial solution for 1 (s), where B d is the boundary of degenerate scale using the fundamental solution U(s, x) = ln(r) [13,[15][16][17][32][33][34]. For determining the degenerate scale systematically from one trial of a normal scale, we provide a flowchart as shown in Figure 2(a) and the numerical results as shown in Table I.…”
Section: Dual Boundary Integral Formulation and Dual Bem For Torsion mentioning
confidence: 99%
“…Chen et al [4] 235 methods to eliminate degenerate scale, scaling method and restriction method were discussed by Christiansen [33]. He also investigated the condition number of the influence matrix of the fictitious BEM and null-field approach [34]. Here, three regularization techniques will be employed to avoid the zero singular value.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Here, rectilinear elements are used and a constant approximation of the functions at each element. It can be shown that the condition number depends on the radius R of the circle and the number of boundary elements N according to…”
Section: Large Condition Numbersmentioning
confidence: 99%